The K2 Galactic Caps Project – going beyond the Kepler field and ageing the Galactic disc. Issue 4 (4th November 2019) - Rendle, B M; Miglio, A; Chiappini, C; Valentini, M; Davies, G R; Mosser, B; Elsworth, Y; García, R A; Mathur, S; Jofré, P; Worley, C C; Casagrande, L; et al.
ABSTRACT: Analyses of data from spectroscopic and astrometric surveys have led to conflicting results concerning the vertical characteristics of the Milky Way. Ages are often used to provide clarity, but typical uncertainties of >40 per cent from photometry restrict the validity of the inferences made. Using the Kepler APOKASC sample for context, we explore the global population trends of two K2 campaign fields (3 and 6), which extend further vertically out of the Galactic plane than APOKASC. We analyse the properties of red giant stars utilizing three asteroseismic data analysis methods to cross-check and validate detections. The Bayesian inference tool PARAM is used to determine the stellar masses, radii, and ages. Evidence of a pronounced red giant branch bump and an [α/Fe] dependence on the position of the red clump is observed from the K2 fields radius distribution. Two peaks in the age distribution centred at ∼5 and ∼12 Gyr are found using a sample with σage < 35 per cent. In comparison with Kepler, we find the older peak to be more prominent for K2. This age bimodality is also observed based on a chemical selection of low-[α/Fe] (≤0.1) and high-[α/Fe] (>0.1) stars. As a function of vertical distance from the Galactic mid-plane (| Z |), the age distribution shows a transition from a young to old stellar population with increasing | Z | for the K2 fields. Further coverage of campaign targets with high-resolution spectroscopy is required to increase the yield of precise ages achievable with asteroseismology.